Remarks on the daily rhythm of Lepidoptera in Simsia amplexicaulis (Cav.) (Asteraceae) in a cloud forest of Veracruz State, Mexico - Hernández-Baz, Fernando; González, Jorge; Carmona Valdovinos, Tomás; Castro Bobadilla, Gerardo (Instituto de Ecología, A.C., 2014)
A total of 424 Lepidoptera specimens (256 males, 168 females) visiting flower patches of Simsia amplexicaulis were collected. They were found to belong to six families within three superfamilies representing a total of 23 species: Papilionoidea: Pieridae (2 species), Lycaenidae (1 species), Riodinidae (2 species), Nymphalidae (6 species); Hesperioidea: Hesperiidae (11 species); and Noctuoidea: Erebidae (1 species). The temporal distribution of these lepidopterans shows a peak of species visiting a patch of flowers between 12:00 and 13:00. Twenty five of the species (93%) were recorded during such activity hourly peak while only two species were found visiting the flowers during most of the day. Twenty species (74%) visited the flowers only once. As far as we know, this is the first time that Cuanopepla bella (Ctenuchidae) is reported visiting flowers of Simsia amplexicaulis.